Letter from Svante Arrhenius to Georg Bredig, September 1898 - Arrhenius, Svante (1898)
Svante Arrhenius (1859-1927) writes to Georg Bredig (1868-1944) with an update on his newest piece, “On the Influence of Air Electricity on Physiological Conditions.” Arrhenius also writes of his new colleagues including Nils Gustaf Ekholm (1848-1923), "Euler", Arthur Rindell (1852-1936), Viktor Rothmund (1870-1927), "Dr. Price", and "Mr. Finkelstein".
Keywords: Arrhenius, Svante, 1859-1927; Bredig, Georg, 1868-1944; Rothmund, Viktor, 1870-1927; Ekholm, Nils Gustaf, 1848-1923; Chemists; Rindell, Arthur, 1852-1936